Needs of older persons undergoing cardiac surgery: Exploring the perceptions of nurses, patients waiting for and patients having had surgery - Soraia Filipa Nicola Martins Rodrigues; Helga Marília da Silva Rafael Henriques; Maria Adriana Pereira Henriques (Wiley, 2022)
Abstract Aims The purpose of this research was to identify the needs of older persons waiting for elective open‐heart surgery. Design A qualitative exploratory design methodology, using Focus Groups. Methods A purposive sampling technique was used. Three interviews were conducted with experienced nurses, individuals waiting for open‐heart surgery (≥65years) and individuals having had open‐heart surgery (≥65years); enrolling up to 17 participants from October 2019 to January 2020. Qualitative data analysis was conducted using the iteractive model and MaxQDA® software, and EQUATOR COREQ guidelines were followed. Results Three themes were identified from the analysis of all three Focus Groups: (i) Needing health information; (ii) Needing emotional support; and (iii) Needing access to care.